Factors Affecting Image and Trust in Private Universities - Astuty, Widia; Pasaribu, Fajar (Budapest International Research and Critics University, 2021)
This research was conducted to reveal the factors that influence the image and trust through service marketing management and customer relations to the image of private universities and their implications for customer trust. The research method used is the explanatory survey method. The unit of analysis in this study is a private university located in North Sumatra Province which is in LLDIKTI I, totaling 222 private universities. The number of samples had taken as many as 73 PTS. Based on the distribution of questionnaires, only 50 private universities were willing and fully included in the unit of analysis so that the number of respondents was 550 people who were selected as the unit of analysis. Data analysis method using Partial Least Square-Path Modeling (PLS-PM).The results of hypothesis testing indicate that the university's image variable is a full intervening variable where it is proven that service marketing management and customer relations do not have a direct influence on customer trust but provide a significant indirect effect. The magnitude of the influence of service marketing management variables, customer relations, and university image shows that the largest influence on customer trust is given by service marketing management, followed by the second place is the image of the university and the third position is customer relations.